2022
DOI: 10.3389/fpubh.2022.913159
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Assertive Community Treatment in Rural and Remote Areas: A Qualitative Study of the Challenges and Adaptations of the Model

Abstract: BackgroundFlexible assertive community treatment (FACT) is an innovative model for providing long-term treatment to people with severe mental illness. The model was developed in the Netherlands but is now used in other countries, including Norway, which has a geography different from the Netherlands, with many rural and remote areas. Implementation of innovations is context dependent. The FACT model's potential in rural and remote areas has not been studied. Therefore, we aimed to gain knowledge regarding the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
(125 reference statements)
1
6
0
Order By: Relevance
“…These results are similar to those of other studies on the use of video conferencing with patients of ACT and FACT teams during the COVID-19 pandemic [12,13], and are also consistent with findings on the use of video conferencing in multidisciplinary team-based treatment in somatic care [15]. This finding also matches a study on adaptations of the FACT model when implemented in rural areas in Norway, which showed that use of video meetings and video consultations were some of the adaptations made [7]. A study on therapists' experiences of the use of video consultation in specialist mental health care during the COVID-19 pandemic highlighted that the therapists were hesitant to talk about the most sensitive themes and subjects.…”
Section: Principal Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…These results are similar to those of other studies on the use of video conferencing with patients of ACT and FACT teams during the COVID-19 pandemic [12,13], and are also consistent with findings on the use of video conferencing in multidisciplinary team-based treatment in somatic care [15]. This finding also matches a study on adaptations of the FACT model when implemented in rural areas in Norway, which showed that use of video meetings and video consultations were some of the adaptations made [7]. A study on therapists' experiences of the use of video consultation in specialist mental health care during the COVID-19 pandemic highlighted that the therapists were hesitant to talk about the most sensitive themes and subjects.…”
Section: Principal Findingssupporting
confidence: 90%
“…Most FACT teams are organized as a cooperation between specialist care and primary care within one or more municipalities. FACT teams in rural areas often include multiple municipalities and are distributed over several locations [7]. The Norwegian government has the responsibility for the specialist mental health care delivered by the hospitals or community mental health centers, owned by four Regional Health Authorities, while primary care and local services are delivered by the 356 municipalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The FACT model fidelity of this team was assessed as strong. 6 For more information on the context of the FACT teams and the leading project, please refer to Brekke et al (2021) and Trane et al (2021Trane et al ( , 2022aTrane et al ( , 2022b.…”
Section: Contextmentioning
confidence: 99%